Upaya Dinas Pariwisata Dan Kebudayaan Dalam Meningkatkan Kunjungan Wisatawan Di Daya Tarik Wisata Pura Kehen Kabupaten Bangli - Prawami, Ni Luh Putu Krisna; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 6 No 1 (2018): VOL 6, NO 1 (2018): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2018.v06.i01.p03, 2018)
The efforts of Culture and Tourism Department as tourism stakeholder demanded to be active, to increase the tourism in Kehen Temple tourist attraction.             This research aims to determine about the efforts of Culture and Tourism Department on increasing tourists visit in Kehen Temple tourist attraction. The data collecting method used in this research are participative observation, interviews, and documentary. This research used qualitative analysis method.             From the result of this research concluded that the efforts done by Culture and Tourism Department of Bangli Regency seen from main task and function of department which written in Act Number 10 Year 2009 about tourism. Those efforts are doing fixes to tourism supporting facilities, promoting Kehen Temple as tourist attraction and held founding to local community. But according to Pokdarwis Giri Manik, the efforts held by Culture and Tourism Department felt not maximum yet.             From the conclusion then suggested for Culture and Tourism of Bangli Regency to promote Kehen Temple tourist attraction more specifically, the found ing to local community not just for Pokdarwis, and special attention on seller kiosks layout around  Kehen Temple tourist attraction.   Key words        : Kehen Temple, Effort of Tourism Department, Improvements, Tourist Visit